Building Adaptive reuse determinants Case study: Al Andalus hospital in Aleppo city: محددات إعادة توظيف الأبنية: دراسة حالة مشفى الأندلس في مدينة حلب - Wajih Mohammed Nasrat Sammani, Saad Eldin Aladdin Zeitoun (Journal of engineering sciences and information technology, 2022)
With the growth and expansion of cities, their requirements change, which calls to Adaptive reuse of their buildings in proportion to these changing requirements in a sustainable manner. Therefore, the aim of the research is to reach the most important axes and determinants of building adaptive reuse process that must be taken into account when thinking about the of building adaptive reuse, through which it is possible to assess the success of building adaptive reuse process Employment, by explaining the concept of building adaptive reuse in addition to reviewing the ARP model to determine the possibility of building adaptive reuse and the ADAPT STAR model to increase the possibility of adaptive reuse in the future, leading to the extraction of the seven main axes of building adaptive reuse and then conducting a questionnaire to determine the relative weights of these axes and determine the impact of each A specific of the determinants of building adaptive reuse on the adaptive reuse process as a whole and on each other, ending by applying the results of the theoretical framework to a practical case of building adaptive reuse in the city of Aleppo. The research reached to extract sub-determinants specific to each of the seven axes regulating building adaptive reuse, and the research recommended the adoption of the extracted model to determine the extent of success of building adaptive reuse and to clarify the weaknesses and strengths of that process.